2014
DOI: 10.1515/rne-2012-0021
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Regulatory Reform Process on the R&D Investment of European Electricity Utilities

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Therefore, industry-wide cooperation has collapsed, economic issues have gained a central role, projects with shorter payback periods are preferred and customer-oriented product innovations have flourished [18]. Moreover, several authors have consistently confirmed a significant reduction in sectoral R&D investments in different jurisdictions after liberalization experiences [19][20][21][22][23][24][25][26]. However, very little is known about how utilities accomplish their innovation strategies at the firm level in a liberalized environment; i.e., which activities (inputs) are needed to generate innovations (outputs).…”
Section: Internal Determinants Of Innovationmentioning
confidence: 99%
“…Therefore, industry-wide cooperation has collapsed, economic issues have gained a central role, projects with shorter payback periods are preferred and customer-oriented product innovations have flourished [18]. Moreover, several authors have consistently confirmed a significant reduction in sectoral R&D investments in different jurisdictions after liberalization experiences [19][20][21][22][23][24][25][26]. However, very little is known about how utilities accomplish their innovation strategies at the firm level in a liberalized environment; i.e., which activities (inputs) are needed to generate innovations (outputs).…”
Section: Internal Determinants Of Innovationmentioning
confidence: 99%
“…Indeed, the European Union has already put vertical disintegration of the high-voltage transmission grid into practice (starting with to the EU directive 1996/92/EC; Schmitt and Kucera, 2013). While the empirical literature in general finds considerable cost savings from vertical economies for US electricity utilities, limited empirical literature on single-country studies points toward modest cost savings in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [26] analyzed the rate of change in the R&D investment for large-scale power generation and transmission facilities in eight European Union (EU) countries, and concluded that both privatization and regulatory reform decrease R&D investment. Furthermore, in order to find the contribution of reform to environmental protection, Ref.…”
Section: Overall Effects Of Market Reform On Electric Power Industrymentioning
confidence: 99%